Integrative Proteomic and Phosphoproteomic Analyses of Granulosa Cells During Follicular Atresia in Porcine - Yang, Feng; Liu, Qiang; Chen, Yanhong; Ye, Huizhen; Wang, Han; Zeng, Shenming (Frontiers in Cell and Developmental Biology, 2021)
Ovarian follicular atresia is a natural physiological process; however, the mechanism is not fully understood. In this study, quantitative proteomic and phosphoproteomic analyses of granulosa cells (GC) in healthy (H), slightly atretic (SA), and atretic follicles (A) of porcine were performed by TMT labeling, enrichment of phosphopeptides and LC-MS/MS analysis. In total, 6,201 proteins were quantified and 4,723 phosphorylation sites of 1,760 proteins were quantified. In total, 24 (11 up, 13 down) and 50 (29 up, 21 down) proteins with a fold change (FC) > 5 were identified in H/SA and H/A, respectively. In addition, there were 20 (H/SA, up) and 39 (H/A, up) phosphosites with an FC > 7, that could serve as potential biomarkers for distinguishing different quality categories of follicles. Western blotting and immunofluorescence confirmed the reliability of the proteomic analysis. Some key proteins (e.g., MIF, beta catenin, integrin β2), phosphosites (e.g., S76 of caspase6, S22 and S636 of lamin A/C), pathways (e.g., apoptosis, regulation of actin cytoskeleton pathway), transcription factors (e.g., STAT5A, FOXO1, and BCLAF1), and kinases (e.g., PBK, CDK5, CDK12, AKT3) involved in atresia process were revealed via further analysis of the differentially expressed proteins (DEPs) and phosphorylated proteins (DEPPs). Further study showed that mutant caspase6 Ser76 to Ala increased the ratios of cleaved caspase6/caspase6 and cleaved caspase3/caspase3, and dephosphorylation of caspase6 at Ser76 increased cell apoptotic rate, a new potential pathway of follicular atresia. Collectively, the proteomic and phosphoproteomic profiling and functional research in the current study comprehensively analyzed the dynamic changes in protein expression and phosphorylation during follicular atresia and provided some new explanations regarding the regulation of this process.